Does Small Retailer Market Orientation Matter for Long‐Term Oriented Relationships with Suppliers?. (16th September 2013) - Chung, Jae‐Eun; Karatas‐Ozkan, Mine; Anderson, Alistair R.; Fayolle, Alain; Howells, Jeremy; Condor, Roland
<x xml:space="preserve">Abstract</x> This study examines the influences of small retailer market orientation on supplier transaction‐specific investment and supplier role performance and the roles of supplier transaction‐specific investment and supplier role performance in determining small retailer long‐term orientation. Data were collected from 102 small independent apparel stores in the United States The results show that small retailer market orientation positively influences supplier transaction‐specific investment, which in turn influences supplier role performance. Supplier transaction‐specific investment and role performance influence small retailer trust, but only supplier transaction‐specific investment positively affects small retailer dependence. Small retailer trust and supplier transaction‐specific investment influence small retailer long‐term orientation.